How Do Households Respond to Job Loss? Lessons from Multiple High-Frequency Data Sets - Asger Lau Andersen; Amalie Sofie Jensen; Niels Johannesen; Claus Thustrup Kreiner; Søren Leth-Petersen; Adam Sheridan (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
How do households respond to job loss, and which self-insurance channels are most important? By linking customer data from the largest bank in Denmark with information from government administrative registers, we quantify a broad range of responses to job loss in a unified empirical framework. Two response margins stand out: during the first 24 months after job loss, households reduce spending by 30% of the income loss while reduced saving in liquid assets accounts for 50%. Other response margins highlighted in the literature - spousal labor supply, private transfers, home equity extraction, mortgage refinancing, and consumer credit - are less important.
Keywords: D14; G51; G52; J65; 330; Household economics; unemployment; self-insurance; transaction data